The Experiences of CLIL Teachers in Finland - Clark, Inka (My University, 2025)
Content and language integrated learning (CLIL) is a pedagogical approach where a second language is used for learning and teaching subject content. Therefore, students develop content knowledge as well as language skills simultaneously. The present study investigates teachers’ experiences in CLIL classrooms in Finland. The study was conducted with 7 primary school CLIL teachers who were based in southern parts of Finland. The data was collected via semi-structured interviews with 14 questions. The findings showed that CLIL teachers have positive experiences such as seeing their pupils’ learning and using the second language and being personally challenged by the different levels within the classroom. The CLIL teachers also face challenging experiences such as the lack of material, internal structures and the language background of the pupils.
Keywords: Content and language integrated learning (CLIL), Bilingual, Second Language, Experience, Challenges, Primary Teachers, Finland